Utilization of Agro-Industrial Wastes and Organic Supplements for Cultivation of Blue Oyster Mushroom - Aditya, -; Jarial , Rajinder Singh (Bangladesh Journal of Botany, 2023)
Mushroom cultivation is a cost-effective biotechnological approach for converting diverse lignocellulosic wastes into nutritionally rich food. Hypsizygus ulmarius is a high yielding mushroom gaining popularity nowadays. In the present study the suitability of various available agro-industrial wastes and supplements for the cultivation of H. ulmarius was evaluated. Results indicated that among the seven locally available substrates, wheat straw substrate was found to be the best substrate as the highest yield (744.08 g/0.6 Kg dry substrate) and biological efficiency (124.00 %) were obtained. Number of sporophores was more in wheat straw substrate while stipe length was longest in pine needles and cap diameter was recorded maximum in maize straw. Moreover, yield was also recorded more in wheat straw supplemented with cotton seed hull significantly followed by the same substrate when added with gram flour and rice bran. However, lowest yield was obtained when no supplement was added in wheat straw. Bangladesh J. Bot. 52(1): 179-185, 2023 (March)